Report of the Steering Committee on Science and Technology for the Formulation of Twelfth Five Year Plan (2012-2017) - Planning Commission (Planning Commission, 2012)
Fundamentals of Indian economy are robust. There are predictions that India would emerge as one of the three or four major global economies. Competitiveness of Nations in knowledge economies are likely to be determined by access to knowledge and technology. India may have to necessarily prepare herself for meeting the challenges of global knowledge economy by investing adequately into knowledge systems such as Research and Development.
Planning Commission Government of India
Planning Commission Government of India